2018
DOI: 10.1007/s12291-018-0753-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Circulating Plasma VEGF-A, ET-1 and Magnesium Levels as the Predictive Markers for Proliferative Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) is the most common cause for preventable blindness in India. The onset of micro and macrovascular complications in T2DM is multifactorial and difficult to predict. The status of micronutrients, several inflammatory cytokines, elevated triacylglycerols, oxidative stress etc., are being studied extensively. Hypomagnesemia plays a pivotal role in worsening of insulin resistance. Although, Vascular Endothelial Growth Factor-A (VEGF-A) and Endothelin-1 (ET-1) are known to be elevated in DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Surprisingly, patients with proliferative retinopathy had higher HDL-C values ( p < 0.05). TC, TG, LDL-C, and VLDL concentrations did not differ significantly among the study groups [ 64 ]. Hruby et al (2017) studied the link between the intake of Mg and the risk of T2DM in three cohorts from the United States of America, detecting a 15% T2DM-risk reduction in individuals with a higher dietary intake of Mg. Hypercholesterolemia was more frequent in the fifth (12.7% for 427–498 mg/day) versus first (8.7% for 242–275 mg/day) quartile of Mg intake, whereas in women the data were conflicting: in one cohort, hypercholesterolemia was more prevalent in the fifth (7.8% for 357–418 mg/day) versus first (6.2% for 187–218 mg/day) quartile of Mg intake, whereas in the other cohort the results were opposite (15.4% for 213–245 mg/day versus 14.4% for 385–448 mg/day) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, patients with proliferative retinopathy had higher HDL-C values ( p < 0.05). TC, TG, LDL-C, and VLDL concentrations did not differ significantly among the study groups [ 64 ]. Hruby et al (2017) studied the link between the intake of Mg and the risk of T2DM in three cohorts from the United States of America, detecting a 15% T2DM-risk reduction in individuals with a higher dietary intake of Mg. Hypercholesterolemia was more frequent in the fifth (12.7% for 427–498 mg/day) versus first (8.7% for 242–275 mg/day) quartile of Mg intake, whereas in women the data were conflicting: in one cohort, hypercholesterolemia was more prevalent in the fifth (7.8% for 357–418 mg/day) versus first (6.2% for 187–218 mg/day) quartile of Mg intake, whereas in the other cohort the results were opposite (15.4% for 213–245 mg/day versus 14.4% for 385–448 mg/day) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Insulin was initially believed to be a vasodilator because of its activation on NO secretion (30,31). However, in recent studies, insulin-induced vasodilation was confirmed to be impaired in insulin-resistant patients, and patients with obesity or insulin resistance have elevated ET-1 concentrations in the blood (32,33). The mechanism underlying the direct vascular effect of insulin on endothelial cells remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes duration, poor glycemic control, nephropathy, hypertension, and dyslipidemia were established as modifiable risk factors for DR [5]. Magnesium deficiency is suggested as a possible novel risk factor for DR for the following reasons: i) Mg serves a fundamental role in energy metabolism, ii) retina is the most metabolically active tissue in the body, hence sensitive to hypoxia, iii) Mg has a vital role in the development and physiological eye function in experimental animal studies [7], [8], [18], [34]. The main result of our present meta-analysis provided evidence that hypomagnesemia and low Mg levels in T2DM patients increased the risk of developing DR (OR 4.52 [2.08, 9.81], p=0.0001; MD -0.30 mg/dL [-0.44, -0.15], p<0.0001).…”
Section: Discussionmentioning
confidence: 99%